The Role of Green Economy in Climate Change Mitigation - Firnando, Hero Gefthi (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Abstract As the world confronts the escalating challenges of climate change, the role of the green economy has come to the forefront in the quest for effective mitigation strategies. This paper, titled